2021
DOI: 10.1001/jamaneurol.2021.0873
|View full text |Cite
|
Sign up to set email alerts
|

Sex Disparities in Enrollment in Recent Randomized Clinical Trials of Acute Stroke

Abstract: IMPORTANCEThe underenrollment of women in randomized clinical trials represents a threat to the validity of the evidence supporting clinical guidelines and potential disparities in access to novel treatments. OBJECTIVE To determine whether women were underenrolled in contemporary randomized clinical trials of acute stroke therapies published in 9 major journals after accounting for their representation in underlying stroke populations.DATA SOURCES MEDLINE was searched for acute stroke therapeutic trials publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 150 publications
0
47
1
1
Order By: Relevance
“…Most participants were male. Although we did not blind the assigned treatment to participants and physicians, the outcomes were objective and adjudicated blinded to treatment allocation, which minimizes bias. Adherence to the allocated treatment decreased over time but was greater than 80% even after 5 years of follow-up and did not seem to be affected by the publication of the main results.…”
Section: Discussionmentioning
confidence: 99%
“…Most participants were male. Although we did not blind the assigned treatment to participants and physicians, the outcomes were objective and adjudicated blinded to treatment allocation, which minimizes bias. Adherence to the allocated treatment decreased over time but was greater than 80% even after 5 years of follow-up and did not seem to be affected by the publication of the main results.…”
Section: Discussionmentioning
confidence: 99%
“…11 For instance, females are less likely than males to be enrolled in clinical trials of acute stroke across all regions and study types. 12,13 In a Japanese prospective registry study of 2,399 patients with AIS-LVO, females were less likely to receive endovascular therapy (47.9% versus 57.7%, p < 0.001). 6 In the current study, a similar phenomenon was observed, with a lower number of female patients than male patients receiving MT at our center over the 3year period studied (126 [36.3%] vs. 221 [63.7%]).…”
Section: Discussionmentioning
confidence: 99%
“…To measure enrollment of females, we used a modified version of the enrollment disparity difference (EDD), a metric which accounts for sex prevalence inequalities in the general population, initially developed to characterize enrollment disparities in lung cancer treatment RCTs, 16 and also used in a recent study of sex enrollment disparities in RCTs of acute stroke therapies. 8 For each RCT, we calculated the proportion of females enrolled in the trial (PFT), and estimated the proportion of females with AF among the general population (PFG) using data from the Global Burden of Disease (GBD) database (https://gbd2017.healthdata.org/gbdsearch/). Each trial was matched to GBD prevalence data on the basis of the approximate median year of the trial recruitment period and geographic area.…”
Section: Assessment Of Sex Enrollment Disparitiesmentioning
confidence: 99%
“…Sex differences in disease pathophysiology, clinical patterns, and response to treatment should be considered in the design, analysis, and reporting of research studies 6,7 . Recent analyses have shown inadequate enrollment of women in randomized controlled trials (RCTs) of various cardiovascular diseases 8–10 . Given the well‐established importance of sex in the epidemiology of AF, 4 the underrepresentation of women in RCTs of therapies for patients with AF might undermine their generalizability and consequently the validity of the evidence guiding treatment of women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation